PENGARUH INFLASI DAN PERTUMBUHAN EKONOMI TERHADAP KEMISKINAN DI SUMATERA BARAT - Maiyasni; Alfi Adha; Deni Setiawan; Idratul Wahyuda; Mukhtar Azima; Ansofino (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to analyze the effect of inflation and economic growth on poverty levels in West Sumatra Province. Poverty remains one of the major development challenges influenced by various macroeconomic factors, including inflation and economic growth. High inflation can reduce people's purchasing power and potentially increase the number of poor residents, while economic growth is expected to create employment opportunities and improve income levels, thereby reducing poverty. This research employs a quantitative approach using secondary data obtained from official publications of the Statistics Indonesia and other relevant sources over a specific observation period. Data analysis is conducted using multiple linear regression to examine the effects of inflation and economic growth on poverty. The results indicate that inflation has a positive effect on poverty levels, whereas economic growth has a negative effect on poverty levels. Simultaneously, inflation and economic growth significantly affect poverty in West Sumatra. These findings suggest that price stability and inclusive economic growth should become key priorities for policymakers in efforts to alleviate poverty.